Research on Characteristic Stress and Constitutive Equation of Confined Sandstone during Damage Evolution Based on Energy Evolution Analysis. (7th July 2019) - Yang, Xiaobin; Cheng, Hongming; Hou, Xin; Nie, Chaogang; Lv, Jiaqi
Abstract : This study implements the cyclic loading-unloading triaxial compression tests with confining pressures of 5, 10, 20, and 30 MPa for determining the characteristic stress and constitutive equation of sandstone during damage evolution. The energy evolution characteristics and transformations are analyzed, the energy proportion evolution law is defined and analyzed, and its process is divided into five stages according to the whole stress-strain curve. Then, the dissipation energy proportion method for determining the characteristic stress is proposed and compared with the lateral strain method and the volumetric strain method, and the differences of characteristic stress determined by the three methods are within the acceptable error range, i.e., the proportion of crack initiation stress and crack damage stress to peak stress are all about 40% and 70%, respectively, and least affected by the confining pressures. The new method has strong maneuverability, clearer response to the damage evolution, better coordination with the damage evolution, and less subjective initiative. In addition, the dissipation energy proportion behavior is captured by fitting function and established a relationship with elastic modulus of sandstone, and then the damage evolution constitutive equation of sandstone is established based on energy proportion. Finally, the theoretical curve and experimental curve of damage evolution are compared according to the five stages of dissipation energy proportion evolution, and the result shows that the damage evolution constitutive equation is reasonable.